Corporate Social Responsibility, Customer Loyalty, and Financial Performance: Empirical Findings from the Islamic Bank - Muhammad Muflih; Radia Purbayati; Hasbi Assidiki Mauluddi (Politeknik Negeri Bandung, 2022)
Great attention to financial performance is the key to building solid competitiveness in the Islamic banking industry. By exploring the role of Islamic banks in social programs, this study estimated the relationship between CSR (corporate social responsibility) and financial performance, either directly or through the mediating role of loyalty. These paths trace the ability of CSR to create customer support for Islamic banks which then gives birth to positive financial performance. This study surveyed 505 Islamic bank customers. To test the direct and indirect relationships between CSR and the financial performance of Islamic banks, this study employed the PLS (partial least square) method. Empirical estimation results showed that CSR convincingly affects financial performance directly and positively. Meanwhile, indirectly, it can connect positively with financial performance through the mediating role of customer loyalty. This study contributes to the development of stakeholder theory. For the industry, this study contributes to determining the direction of CSR development, which has implications for increasing the organization's public support and financial performance.